Impairment of endothelial‐mesenchymal transformation during atrioventricular cushion formation in Tmem100 null embryos. Issue 1 (7th November 2014) - Mizuta, Ken; Sakabe, Masahide; Hashimoto, Aya; Ioka, Tomoko; Sakai, Chihiro; Okumura, Kazuki; Hattammaru, Miwa; Fujita, Masahide; Araki, Mutsumi; Somekawa, Satoshi; Saito, Yoshihiko; Nakagawa, Osamu
<x xml:space="preserve">Abstract</x> Background: Endothelial‐mesenchymal transformation (EndMT) is essential for endocardial cushion formation during cardiac morphogenesis. We recently identified Tmem100 as an endothelial gene indispensable for vascular development. In this study, we further investigated its roles for EndMT during atrioventricular canal (AVC) cushion formation. Results:Tmem100 was expressed in AVC endocardial cells, and Tmem100 null embryos showed severe EndMT defect in the AVC cushions. While calcineurin‐dependent suppression of vascular endothelial growth factor (VEGF) expression in the AVC myocardium is important for EndMT, significant up‐regulation of Vegfa expression was observed in Tmem100 null heart. EndMT impaired in Tmem100 null AVC explants was partially but significantly restored by the expression of constitutively‐active calcineurin A, suggesting dysregulation of myocardial calcineurin‐VEGF signaling in Tmem100 null heart. Moreover, Tmem100 null endocardial cells in explant culture did not show EndMT in response to the treatment with myocardium‐derived growth factors, transforming growth factor β2 and bone morphogenetic protein 2, indicating involvement of an additional endocardial‐specific abnormality in the mechanism of EndMT defect. The lack of NFATc1 nuclear translocation in endocardial cells of Tmem100 null embryos suggests impairment of endocardial calcium signaling. Conclusions: The Tmem100 deficiency causes EndMT defect during AVC cushion formation possibly via disturbance of multiple calcium‐related signaling events. Developmental Dynamics 244:31–42, 2015. © 2014 Wiley Periodicals, Inc.